Design of recombinant protein-based SARS-CoV entry inhibitors targeting the heptad-repeat regions of the spike protein S2 domain - Ni, Ling (Biochem Biophys Res Commun, 2005)
Entry of SARS-CoV into a target cell is initiated by binding of the S1 domain of spike protein to a receptor, followed by conformational changes of the spike protein S2 domain, resulting in the formation of a six-helix bundle by the heptad-repeat (HR1 and HR2) regions. Our previous studies have demonstrated that peptides derived from HR2 region could inhibit SARS-CoV entry. However, synthesis of these peptides is at high cost. In this study, we designed two recombinant proteins, one containing two HR1 and one HR2 peptides (denoted HR121), and the other consisting of two HR2 and one HR1 peptides (designated HR212). These two proteins could be easily purified with the low cost of production, exhibiting high stability and potent inhibitory activity on entry of the HIV/SARS pseudoviruses with IC(50) values of 4.13 and 0.95 μM, respectively. These features suggest that HR121 and HR212 can serve as potent inhibitors of SARS-CoV entry.